Possible anti‐obesity effects of phytosterols and phytostanols supplementation in humans: A systematic review and dose–response meta‐analysis of randomized controlled trials - Ghaedi, Ehsan; Varkaneh, Hamed Kord; Rahmani, Jamal; Mousavi, Seyed Mohammad; Mohammadi, Hamed; Fatahi, Somaye; Pantovic, Ana; Darooghegi Mofrad, Manije; Zhang, Yong (Phytotherapy research, 2019)
Present meta‐analysis investigates the effects of phytosterols and phytostanol (PS) supplementation on anthropometric indices, using data from randomized controlled trials. We performed a systematic search in the databases: PubMed, Scopus, Cochran, and Web of Science. Weighted mean difference (WMD) with 95% confidence intervals (CIs) were presented. Overall, 79 randomized controlled trials investigated the effects of PS on anthropometric indices. Meta‐analysis results did not reveal any significant effect of PS supplementation on weight (66 trials‐WMD: −0.083 kg; CI [−0.233, 0.066]; I2 = 42.5%), percentage fat mass (6 trials‐WMD: −0.090%; CI [−0.789, 0.610]; I2 = 0.0%), and waist circumference (WC; 5 trials‐WMD: −0.039 cm; CI [−0.452, 0.374]; I2 = 0.0%). However, body mass index (BMI) significantly decreased after PS supplementation (39 trials‐WMD: −0.063 kg/m2, p = 0.024, I2 = 25.1%). Subgroup analyses showed that PS supplementation in subjects with baseline BMI ≥25 and hyperlipidemic significantly decreased body weight and BMI. The overall results showed that although PS supplementation did not affect anthropometric indices (except BMI), baseline status regarding BMI and hyperlipidemia and also dose and duration could be contributing factors for favorable effects.